1999
DOI: 10.1007/s004320050295
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy in the treatment of recurrent glioblastoma multiforme: ifosfamide versus temozolomide

Abstract: Ifosfamide treatment might be a feasible approach, but it necessitates hospitalization. Temozolomide showed promising results. Due to its oral application, the patient's quality of life (time out of hospital) is favorable. Subgroups with improved survival were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…A new methylating compound, temozolomide (TZM), has recently demonstrated good single-agent activity and acceptable safety profile in phase II and III clinical trials for the treatment of recurrent high-grade gliomas (Bower et al, 1997;Paulsen et al, 1999;Yung et al, 1999Yung et al, , 2000Osoba et al, 2000aOsoba et al, , 2000bBrada et al, 2001;Macdonald, 2001). Moreover, TZM positively affected the neurological function and maintained or improved the quality of life of neoplastic patients (Osoba et al, 2000a(Osoba et al, , 2000b.…”
Section: Introductionmentioning
confidence: 98%
“…A new methylating compound, temozolomide (TZM), has recently demonstrated good single-agent activity and acceptable safety profile in phase II and III clinical trials for the treatment of recurrent high-grade gliomas (Bower et al, 1997;Paulsen et al, 1999;Yung et al, 1999Yung et al, , 2000Osoba et al, 2000aOsoba et al, , 2000bBrada et al, 2001;Macdonald, 2001). Moreover, TZM positively affected the neurological function and maintained or improved the quality of life of neoplastic patients (Osoba et al, 2000a(Osoba et al, , 2000b.…”
Section: Introductionmentioning
confidence: 98%
“…Temozolomide (3-methyl-4-oxo-3,4-dihydroimidazo [5,1-d] [1,2,3,5] tetrazine-8-carboxamide) (TMZ), a relatively new alkylating (methylating) agent, has received much attention, notably in the treatment of malignant gliomas. Phase II and III trials for recurrent high-grade gliomas have revealed that 50 to 60% of glioblastomas, the most malignant form, showed an objective response or stable disease with this compound (1)(2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…Temozolomide (3-methyl-4-oxo-3,4-dihydroimidazo [5,1-d] [1,2,3,5] tetrazine-8-carboxamide) (TMZ), a relatively new alkylating (methylating) agent, has received much attention, notably in the treatment of malignant gliomas. Phase II and III trials for recurrent high-grade gliomas have revealed that 50 to 60% of glioblastomas, the most malignant form, showed an objective response or stable disease with this compound (1)(2)(3)(4). A more recent European Organisation for Research and Treatment of Cancer/National Cancer Institute of Canada trial on concomitant and adjuvant TMZ in addition to radiotherapy as the first-line treatment for glioblastomas demonstrated an increase in median survival from 12.1 to 14.6 months and an increase in the 2-year survival rate from 10 to 26% as compared to radiotherapy alone (5).…”
Section: Introductionmentioning
confidence: 99%
“…Most chemotherapeutic agents tested to date show only marginal, if any, clinical benefit. Temozolomide is a recent addition to the chemotherapeutic arsenal, and phase III clinical trials for temozolomide treatment of recurrent high-grade glioblastomas have shown responses to the drug, reflected in an increased progression-free survival (Bower et al, 1997;Paulsen et al, 1999;Janinis et al, 2000;Yung et al, 2000) The alkylating agent temozolomide is a second-generation imidazotetrazine prodrug. It can be administered orally and has a bioavailability of almost 100%.…”
mentioning
confidence: 99%